COPYWRITING SEBAGAI UPAYA PENINGKATAN PROMOSI DIGITAL: PELATIHAN BAGI KELOMPOK SADAR WISATA DI DESA JATILUWIH, BALI - Utami, Ni Made Verayanti; Putu Desi Anggerina Hikmaharyanti; I Gusti Agung Sri Rwa Jayantini3; Ni Nyoman Deni Ariyaningsih; Gede Irwandika (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
This community service assesses the Tourism Awareness Community in Jatiluwih Village, Tabanan-Bali, focusing on their use of social media for digital promotion. The group utilizes Instagram and Facebook for this purpose. Challenges observed include ineffective promotional language and limited understanding of tourism marketing tools among community members. The intervention provided copywriting and SEO training, covering basics, English usage, persuasive language, and AI integration for content creation on both the village's website and social media. The approach involves observation, interviews, and evaluation. Consequently, the community has shown improvement in understanding copywriting strategies, enhancing their digital promotion efforts on their social media accounts.